Trends in research on sick sinus syndrome: A bibliometric analysis from 2000 to 2022 - Zhang, Xin’ai; Zhao, Yong; Zhou, Yutong; Lv, Jiayu; Peng, Jiaran; Zhu, Haiyan; Liu, Ruxiu (Frontiers in Cardiovascular Medicine, 2022)
Sick sinus syndrome (SSS) is a refractory arrhythmia disease caused by the pathological changes of sinoatrial node and its adjacent tissues. 2,251 publications related to SSS were retrieved from Web of Science database from 2000 to 2022 and analyzed by using VOS viewer and Citespace software. The results showed the United States dominated the field, followed by Japan, Germany and China. Ellenbogen KA was the most prolific researcher and Pace Pacing and Clinical Electrophysiology was the most prolific journal on SSS. Sick sinus syndrome, atrial fibrillation and sinus node dysfunction were the top three keywords that had the strongest correlation with the study. Pacemaker implantation, differentiation and mutation are research hotspots currently. Notably, research on the differentiation and mutation of SSS were relatively limited, which is full of opportunities. In conclusion, bibliometric analysis provided valuable information for the prevention, treatment and future research trends of SSS.